Impact of dyslipidemia on the severity of symptomatic lumbar spine degeneration: A retrospective clinical study - Huang, Zhonglian; Chen, Jiechen; Su, Yihong; Guo, Muxin; Chen, Youbin; Zhu, Yilin; Nie, Guangshuai; Ke, Ruitian; Chen, Hongjiang; Hu, Jun (Frontiers in Nutrition, 2022)
Background Little is known about the relationship of dyslipidemia to the risk of intervertebral disc degeneration (IVDD) in Chinese populations. The aim of this study was to assess the impact of serum lipid levels on the severity of lumbar disc degeneration and to investigate its association with endplate inflammation. Materials and Methods We conducted a case retrospective study in which a total of 302 Chinese hospitalized patients were recruited, of whom 188 without underlying disease, while the rest 114 patients had underlying diseases. We examined fasting serum lipid levels for total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C). Magnetic resonance imaging (MRI) results were used to determine the endplate inflammation. Pfirrmann grading and Weishaupt grading were used to evaluate the severity of intervertebral disc degeneration and facet joint degeneration, respectively. Result TG and HDL-C showed no significant difference (P=0.064, P=0.336). The multivariate logistic regression model showed that age was a risk factor for the occurrence of endplate inflammation. In the group without underlying diseases, age may be a risk factor for the occurrence of endplate inflammation (P<0.01). In the group with underlying diseases, all indicators of patients were not directly related to the occurrence of endplate inflammation (P>0.05). A nonlinear machine learning model was used to measure the contribution of each factor to the disease outcome and to analyse the effect between the top 3 contribution factors and the outcome variables. In the patients without underlying diseases, the top three factors contributing to the severity grading of both IVDD and facet joint degeneration were age, HDL-C, and TG. For the patients with underlying diseases, the top three factors contributing to intervertebral disc degeneration were age, BMI and LDL-C/HDL-C. In terms of degree classification, the top three contributing factors were age, BMI, and TC. Conclusion This study shows that high-density lipoprotein and triglycerides have important effects on the degree of degeneration in patients with symptomatic lumbar degeneration without underlying diseases. There is no clear association between dyslipidemia and the occurrence of endplate inflammation in both groups.